Distribution, prevalence and a new race of Puccinia graminis avenae in Rio Grande do Sul - Coelho, Elisa Thomaz (Pesquisa Agropecuaria Brasileira, 2014)
Isolates from samples collected in Rio Grande do Sul, Brazil, from 1970 to 1972 were studled in continuation of previous surveys of physiologically different races of Puccinia graminis Pers f. sp. avenae Eriks & Henn. The races 3A, 3B, 3C, 4A, 4B, 4C, 4D, 6B, 7A and 7C were identified. The race 4C was isolated for the first time in 1971. The most frequent race was 3C. Race 3A was the second most prevalent in 1970 and 1972, and race 4C in 1971. The percentage of races most prevalent from 1959 to 1972 are presented. A comparative study of local races and of those described in the modified international system of Stewart & Roberts (1970) was observed. The differential variety Eagle2 x CI 4023 (gene pg 8) was resistant to all isolates studied.